2016
DOI: 10.1186/s13059-016-1093-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding rare and common diseases in the context of human evolution

Abstract: The wealth of available genetic information is allowing the reconstruction of human demographic and adaptive history. Demography and purifying selection affect the purge of rare, deleterious mutations from the human population, whereas positive and balancing selection can increase the frequency of advantageous variants, improving survival and reproduction in specific environmental conditions. In this review, I discuss how theoretical and empirical population genetics studies, using both modern and ancient DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 205 publications
(302 reference statements)
4
68
0
1
Order By: Relevance
“…Instead, we show that proteins enriched in rare variants are, based on the associated functional pathways, most similar to those enriched in common variants (Figure 8). Moreover, our results show that population variants implicate functions mainly associated with environmental response (Figure 3), in agreement with results from evolutionary studies reviewed in [84].…”
Section: Rare Variants Are Similar To Common Variantssupporting
confidence: 91%
“…Instead, we show that proteins enriched in rare variants are, based on the associated functional pathways, most similar to those enriched in common variants (Figure 8). Moreover, our results show that population variants implicate functions mainly associated with environmental response (Figure 3), in agreement with results from evolutionary studies reviewed in [84].…”
Section: Rare Variants Are Similar To Common Variantssupporting
confidence: 91%
“…A well-known example of this phenomenon is described above for the FUT2 gene. The maintenance of multiple ABO histo-blood groups, which most likely resulted from the selective pressure exerted by different pathogens, is also due to balancing selection (reviewed in (Quintana-Murci, 2016)). Several works have indicated that targets of balancing selection in primate genomes have often evolved in response to pathogen-driven selective pressures (Leffler et al, 2013;Ferrer-Admetlla et al, 2008;Azevedo et al, 2015;Fumagalli and Sironi, 2014), making overdominance an appealing model to test for resistance against infection.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, these genetic variants are associated with a decreased risk of the disease and with clinicopathological parameters related to good prognosis. In general, it is expected that due to a natural selection effect the protective genetic variant becomes predominant over the time in a population . In this vein, it is conceivable that these SNPs may constitute recent events, which have not yet reached equilibrium among descendants.…”
Section: Discussionmentioning
confidence: 99%